GOVERNMENT POLICIES IN HANDLING AND OVERCOMING THE PROBLEMS OF THE COVID-19 PANDEMIC IN INDONESIA - Kurhayadi, Kurhayadi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2021)
This research will be carried out to see how the policies made by the Indonesian government can overcome and suppress the spread of Covid-19. In practice, this research will use a qualitative approach. This research method will use a literature study. The data used in this study came from various research results and previous studies that are still relevant to this research. This study found that the Indonesian government has implemented various policies to overcome the problems of the Covid-19 pandemic. Several policies that the government has implemented include policies to stay at home, carry out large-scale social restrictions, limit physical interaction, always use personal protective equipment such as masks, always maintain personal hygiene, do learning and work from home, stop various activities that cause a lot of people to gather, and finally implement the new normal policy. In addition to these various policies, the government has also implemented policies in the form of social protection and social assistance to provide guarantees to the community to be able to survive during the pandemic.